IlvHI locus of Salmonella typhimurium. - Squires, C H (1983)
In Escherichia coli K-12, the ilvHI locus codes for one of two acetohydroxy acid synthase isoenzymes. A region of the Salmonella typhimurium genome adjacent to the leucine operon was cloned on plasmid pBR322, yielding plasmids pCV47 and pCV49 (a shortened version of pCV47). This region contains DNA homologous to the E. coli ilvHI locus, as judged by hybridization experiments. Plasmid pCV47 did not confer isoleucine-valine prototrophy upon either E. coli or S. typhimurium strains lacking acetohydroxy acid synthase activity, suggesting that S. typhimurium lacks a functional ilvHI locus. However, isoleucine-valine prototrophs were readily isolated from such strains after mutagenesis with nitrosoguanidine. In one case we found that the Ilv+ phenotype resulted from an alteration in bacterial DNA on the plasmid (new plasmid designated pCV50). Furthermore, a new acetohydroxy acid synthase activity was observed in Ilv+ revertants; this enzyme was similar to E. coli acetohydroxy acid synthase III in its lack of activity at low pH. This new activity was correlated with the appearance in minicells of a new polypeptide having an approximate molecular weight of 61,000. Strains carrying either pCV49 or pCV50 produced a substantial amount of ilvHI-specific mRNA. These results, together with results from other laboratories, suggest that S. typhimurium has functional ilvB and ilvG genes and a cryptic ilvHI locus. E. coli K-12, on the other hand, has functional ilvB and ilvHI genes and a cryptic ilvG locus.